Living Free from Personal Debt: A Possibility or A Mere Wish? - Fonkem, Beryl Ngum (Advances in Social Sciences Research Journal, 2024)
The steady growth in personal debt over the years in the United States is beginning to raise concerns because people are slowly drowning in debt, and it is taking a huge toll on their everyday lives, their relationships, and their mental health. People are increasingly getting stressed, anxious, and depressed because the debts are overwhelming, and the payments are becoming difficult because of growing inflation and high interest rates. 8 out of every 10 adult Americans are reportedly drowning in debt, and it cuts across young adults to older adults who are retiring with debts. Debt is generally categorized as good debt and bad debt – good debt (student loans, business loans, and mortgages) is owed on things that will build wealth in the future, while bad debt (auto loans, credit cards, personal loans, payday loans) hardly improves one’s financial stability. This paper examines how possible it is to become debt-free and establishes that it is a journey that requires some level of discipline and positivity and will take a while to accomplish for anyone who is determined to get out of debt.